Extraction and Characterization of Tobacco Seed Oil - Mukhtar, Azam; Ullah, Habib; Mukhtar, Hamid (Asian Journal of Chemistry, 2010)
The present study describes the extraction and characterization of tobacco seed oil. The oil was extracted using soxhlet apparatus and it was found that tobacco seeds were rich in oil content, which was 40.6% by weight. Some of the physical and chemical characteristics of the oil such as specific gravity, iodine value, drying index, saponification value, acid value and unsaponifiable matter were also determined. The values of these parameters were found to be 0.917, 140.27, 5367, 189.3 mg KOH/g, 6.8 mg KOH/g and 1.2, respectively. The results showed that tobacco seed oil was comparable to the other commonly used vegetable oils.